Pengaruh Media Sosial Instagram @tmiiofficial Terhadap Minat Berkunjung ke TMII - Agung Rachman; Rindana Intan Emeilia (JURNAL ILMIAH NUSANTARA, 2024)
This study examines the influence of the Instagram account @tmiiofficial on people's interest in visiting Taman Mini Indonesia Indah (TMII). This study uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to 100 respondents aged 20-40 years, who are followers of the Instagram account @tmiiofficial. The theoretical framework of this study is based on the Stimulus-Organism-Response (SOR) theory which states that stimuli from social media can influence individual responses. The results of the study indicate that the independent variable (social media) has a significant influence on the dependent variable (interest in visiting), with a contribution of 43.6%. The other 56.4% is influenced by other factors not examined in this study. These findings indicate that the Instagram account @tmiiofficial has an influence on increasing interest in visiting TMII. This indicates that social media is a valuable component as a marketing communication strategy for TMII.